Implementasi Program Keluarga Harapan (PKH) di Kecamatan Lubuk Begalung Kelurahan Gurun Laweh Nan XX: Tinjauan terhadap Efektivitas Pendataan dan Ketepatan Sasaran - Ulya Sabina Putri; Artha Dini Akmal (Lembaga Yasin AlSys, 2026)
Program Keluarga Harapan (PKH) is one of the government’s social assistance programs aimed at reducing poverty and improving the welfare of poor and vulnerable communities through assistance in education, health, and social welfare. However, the implementation of this program still faces problems related to the effectiveness of data collection and the accuracy of beneficiary targeting. This study aimed to analyze the implementation of PKH in Lubuk Begalung Subdistrict, Gurun Laweh Nan XX Urban Village, with a focus on the effectiveness of data collection and the accuracy of beneficiary targeting. This study used a qualitative method with a descriptive approach. Data were collected through interviews, observation, and documentation involving informants from the Social Affairs Office, PKH facilitators, urban village officials, and beneficiary communities. Data were analyzed through the stages of data reduction, data display, and conclusion drawing. The results showed that the implementation of PKH had administratively proceeded according to procedures, but substantively it was not yet optimal. The main problem lay in the weak validation and updating of beneficiary data, resulting in targeting inaccuracies, both in the form of inclusion error and exclusion error. In addition, the lack of field verification, data inconsistency among institutions, and limited public access to complaint mechanisms also hindered the effectiveness of the program. This condition resulted in some poor families still not receiving assistance, while some beneficiaries no longer met the criteria. This study emphasizes the importance of strengthening an accurate and sustainable data collection system, improving interinstitutional coordination, and optimizing the role of facilitators and community participation in data verification. The implications of this study indicate that the effectiveness of PKH implementation depends heavily on the quality of data governance and verification mechanisms so that the program is more accurately targeted and has a tangible impact on improving the welfare of poor communities.